2008
DOI: 10.1152/japplphysiol.00893.2007
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic plethysmography measures breathing in unrestrained neonatal mice

Abstract: Measurement of breathing volumes in neonatal mice is of growing importance in order to characterize the influence of development and genetic modifications on respiratory control to evaluate hypotheses concerned with human infant deficits that may affect sudden infant death syndrome, for example. Current techniques require undesirable physical constraints or incur possible artifacts specific to very small animals. We have examined the utility of a recently proposed approach using an acoustic resonance procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Statistical analysis of the results of several recordings showed that the mean values of respiratory parameters in anesthetized mice were reproducible and comparable with values previously reported (Daubenspeck et al, 2008; Hamelmann et al, 1997; Hoymann, 2007; Huang et al, 2011). Several studies reported that the breathing frequency decreases by about 40–60% in anesthetized mice compared with conscious mice (Hamelmann et al, 1997; Takezawa et al, 1980).…”
Section: Discussionsupporting
confidence: 88%
“…Statistical analysis of the results of several recordings showed that the mean values of respiratory parameters in anesthetized mice were reproducible and comparable with values previously reported (Daubenspeck et al, 2008; Hamelmann et al, 1997; Hoymann, 2007; Huang et al, 2011). Several studies reported that the breathing frequency decreases by about 40–60% in anesthetized mice compared with conscious mice (Hamelmann et al, 1997; Takezawa et al, 1980).…”
Section: Discussionsupporting
confidence: 88%
“…; Bissonnette & Knopp, ), a method that directly measures the pressure changes due to inspiration, and they are also consistent with values obtained by acoustic plethysmography in newborn mice (Daubenspeck et al . ). In adult mice, V T can be measured with whole‐body plethysmography with an error <7% of that measured by direct plethymography or pneumotachography (Onodera et al .…”
Section: Discussionmentioning
confidence: 97%
“…The total volume of the cannula was 130 mL; the tidal volume of a mouse being ~8 mL/g. 13,14 At the time of intubation, the tubing of the cannula was stiffened by insertion of a piece of copper wire via the luer lock adaptor (Figure 2B); the wire being removed immediately after intubation. The cannula, tilted so that the luer lock end was slightly lower (~10 o ) than the tip, was inserted as soon as the vocal cords separated.…”
Section: Resultsmentioning
confidence: 99%